Bacterial analysis of biofilms from tooth root surfaces presenting different caries activity - Sandra Liana Henz; Nailê Teixeira Damé; Cristiane Neves Portugal; Marisa Maltz (Universidade Federal do Rio Grande do Sul. Faculdade de Odontologia, 2020)
This study evaluated the numbers and determined the proportion of mutans streptococci and Lactobacillus spp., which are possible relevant cariogenic organisms, in biofilms recovered from lesions at root surfaces with active caries lesions (ARC), inactive caries lesions, and sound root surfaces (SRS). Samples were cultured in MSB agar for mutans streptococci counts, Rogosa agar for Lactobacillus spp. counts, and brain-heart infusion agar for total viable anaerobic counts. After incubation, the number of colony-forming units (CFUs) was determined and compared between groups by the Mann-Whitney U test with a significance level set at 95%. The proportion of counts of mutans streptococci and Lactobacillus spp. in the total viable microorganisms was also analyzed by Chi-square test. Ninety samples (30 from each surface) from 37 patients were cultured and analyzed. The CFU was similar between mutans streptococci and Lactobacillus spp. These species were present in at least half of the samples and no difference was found in the frequency of isolation of these species. Only 6 samples showed a proportion of more than 10% of mutans streptococci; 4 of the samples were from ARC. Most (93%) SRS samples did not contain viable Lactobacillus spp. The data indicate the low counts of mutans streptococci and Lactobacillus spp. in root surfaces, regardless of the activity of caries lesions.